2016
DOI: 10.1111/nph.13874
|View full text |Cite
|
Sign up to set email alerts
|

The jasmonate‐responsive AaMYC2 transcription factor positively regulates artemisinin biosynthesis in Artemisia annua

Abstract: SummaryThe plant Artemisia annua is well known due to the production of artemisinin, a sesquiterpene lactone that is widely used in malaria treatment. Phytohormones play important roles in plant secondary metabolism, such as jasmonic acid (JA), which can induce artemisinin biosynthesis in A. annua. Nevertheless, the JA-inducing mechanism remains poorly understood.The expression of gene AaMYC2 was rapidly induced by JA and AaMYC2 binds the G-boxlike motifs within the promoters of gene CYP71AV1 and DBR2, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
214
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 220 publications
(218 citation statements)
references
References 54 publications
4
214
0
Order By: Relevance
“…Compared with well-studied metabolic pathways such as flavonoids, the transcriptional regulation of terpene metabolism has been validated in a few studies. Several TFs have been identified from plants including A. annua (AaWRKY1, AaERF1, AaERF2, AabZIP1, and AaMYC2), Gossypium arboretum (GaWRKY1), Taxus chinensis (TaWRKY1), Hevea brasiliensis (EREBP1 and HbWRKY1), and O. sativa (OsTGAP1) that regulate terpene biosynthesis [21,22,23,42,43,44,45,46,47,48]. In Mentha species M. spicata , two TFs MsYABBY5 and MsMYB ( M. spicata MYB DNA-binding protein) have been reported that negatively regulate monoterpene production [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with well-studied metabolic pathways such as flavonoids, the transcriptional regulation of terpene metabolism has been validated in a few studies. Several TFs have been identified from plants including A. annua (AaWRKY1, AaERF1, AaERF2, AabZIP1, and AaMYC2), Gossypium arboretum (GaWRKY1), Taxus chinensis (TaWRKY1), Hevea brasiliensis (EREBP1 and HbWRKY1), and O. sativa (OsTGAP1) that regulate terpene biosynthesis [21,22,23,42,43,44,45,46,47,48]. In Mentha species M. spicata , two TFs MsYABBY5 and MsMYB ( M. spicata MYB DNA-binding protein) have been reported that negatively regulate monoterpene production [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…But the transcriptional regulation mechanism is not clear. In recent years, there have been characterized several TFs which could directly bind to the promoters of the aretmisinin biosynthetic genes and regulate the artemisinin content in A. annua (Ma et al, 2009; Yu et al, 2012; Lu et al, 2013a; Shen et al, 2016). Furthermore, a novel TF, AaHD1 (HOMEODOMAIN PROTEIN 1), which belongs to the homeodomain-leucine zipper TF family was identified by our lab (Yan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Artemisia annua used in this study was “Huhao 1,” which obtained from Chongqing, China and developed in Shanghai after years of selection (Shen et al, 2016). A. annua seeds were sown in pots filled with compost and placed in a growth chamber under the growth condition described previously (Zhang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the WT, overexpression of AaMYC2 significantly increased the content of artemisinin and DHAA in transgenic A. annua . Meanwhile, the content of artemisinic acid, which was the competitive pathway product, was significantly reduced in AaMYC2 overexpressing lines (Shen et al, 2016). …”
Section: Plant Metabolic Engineering Strategies For Production Of Phamentioning
confidence: 99%